Recent reproductive coercion and unintended pregnancy among female family planning clients - Miller, Elizabeth; McCauley, Heather L.; Tancredi, Daniel J.; Decker, Michele R.; Anderson, Heather; Silverman, Jay G. (Contraception (Stoneham), 2014)
Reproductive coercion (RC) — birth control sabotage and coercion by male partners to become pregnant and to control the outcome of a pregnancy — has been associated with a history of both intimate partner physical and sexual violence (IPV) and unintended pregnancy among females utilizing reproductive health services. The temporal nature of associations of RC and unintended pregnancy (distinct from the impact of IPV), however, has remained less clear. A survey was administered to females aged 16–29 years seeking care in 24 rural and urban family planning clinics in Pennsylvania (n=3539). Five percent of respondents reported RC in the past 3 months, and 12% reported an unintended pregnancy in the past year. Among those who reported recent RC, 21% reported past-year unintended pregnancy. Compared to women exposed to neither condition, exposure to recent RC increased the odds of past-year unintended pregnancy, both in the absence of a history of IPV [adjusted odds ratio (AOR) 1.79, 1.06–2.03] and in combination with a history of IPV (AOR 2.00, 1.15–3.48); history of IPV without recent RC was also associated with unintended pregnancy (AOR 1.80, 1.42–2.26). Findings indicate the temporal proximity of the association of RC and unintended pregnancy, with recent RC related to past-year unintended pregnancy, both independently and in combination with a history of IPV. Recent RC is relatively prevalent among young women using family planning clinics and is associated with increased risk for past-year unintended pregnancy even in the absence of IPV. Recent RC and a history of IPV are prevalent among female family planning clients, particularly younger women, and these experiences are each associated with unintended pregnancy. Pregnancy prevention counseling should include not only assessment for physical and sexual partner violence but also specific inquiry about RC.